Endogenous ω-3 fatty acids in Fat-1 mice attenuated depression-like behaviors, spatial memory impairment and relevant changes induced by olfactory bulbectomy. (August 2021) - Gu, Minqing; Li, Xiaohong; Yan, Ling; Zhang, Yongping; Yang, Longen; Li, Shurui; Song, Cai
Highlights: Endogenous n -3 in Fat-1 mice could reverse OB-induced depression-like behaviors and spatial memory impairment. Endogenous n -3 PUFAs in Fat-1 mice significantly balanced astrocyte A1 and A2 phenotype expression through the up-regulation S100 β /BDNF ratio. Endogenous n -3 PUFAs in Fat-1 mice significantly reduced macrophage activity and n -6 fatty acid, arachidonic acid (AA) content in the brain. Abstract: Objectives: Olfactory bulbectomy (OB) induced behaviors, hypercortisolism, inflammation and neurotrophin dysfunctions are similar to those observed in depressed patients. Omega (n)-3 polyunsaturated fatty acids (PUFAs) can effectively treat depression via anti-inflammatory and neuroprotective effects. However, n -3 PUFA purities, caloric contents, and ratios in different diets often cause contradictive results. This study used Fat-1 mice, which can convert n- 6 to n -3 PUFAs in the brain, to study the effect of n- 3 PUFAs on OB-induced behaviors and related changes. Methods: Fat-1 and wild-type littermates were fed safflower oil for 3 months. Behaviors were tested on day 21 after surgery. Monoamine neurotransmitters were measured by HPLC. Macrophage activity was measured by MTT assay. Astrocyte phenotypes A1 S100 β, A2 BDNF and cholesterol level were measured by ELISA and total cholesterol assay kits respectively. PUFA profile and membrane fluidity were detected by GC and DPH fluorescence probe respectively. Results: OB significantly induced animal hyperactivity and spatial memory impairment, while decreased sucrose consumption and social contact with decreased 5-HT turnover, increased the macrophage activity and S100 β /BDNF ratio. Meanwhile, n- 3/ n- 6 PUFAs ratio and total cholesterol level were reduced in OB mice. Whereas, OB-induced behavioral changes were attenuated, which were associated with increasing 5-HT turnover, decrease macrophage activity, restored S100 β /BDNF and n- 3/ n- 6 PUFAs ratios, and total cholesterol concentrations in Fat-1 mice. Conclusion: The present study for the first time demonstrated that endogenous n- 3 PUFAs attenuated OB-induced depression-like behaviors and spatial memory impairment through modulating serotonergic and immune function, balancing the astrocyte A1/A2 phenotypes, and normalizing PUFAs profile and membrane function.